P- 79 LIVER TRANSPLANTATION FOR HEPATOCELLULAR, LOOKING FOR THE BETTER SELECTION CRITERIA. RESULTS FROM THE URUGUAYAN LIVER TRANSPLANT PROGRAM - Cinthya Coronado; Josemaría Menéndez; Alejo Gestal; Victoria Mainardi; Solange Gerona (Annals of Hepatology, 2023)
Introduction and Objectives: Liver transplantation (LT) is an established therapeutic in hepatocellular carcinoma (HCC). Since 90’ Milan's criteria have been the gold standard for the selection of the best candidate. In the last decade, new expanded criteria have been developed, like UCSF, Up to 7 and AFP Model, with the purpose of achieving a better selection of liver transplant candidates. This study aimed to describe the results of LT for HCC in our center, evaluate different selection criteria, and assess survival. Materials and Methods: Retrospective analysis of adult patients transplanted with HCC in the National Liver Transplant Program of Uruguay (07/2009-06/2022). Results: Of 259 LT performed, 63 (23,9%) had HCC. Study Population: Age:57 ± 7 years, 82% males. Etiology: 32% hepatitis C, 32% alcohol, 13% NASH, 9% Autoimmune Hepatitis, 5% hepatitis B, 9% others. The median waiting list time is 68 days. At listing: median serum AFP 56 ± 160 ng/L, real MELD-Na 13 points, assigned supplementary 22 points in all diagnosed cases. 48.3% had locoregional treatments before transplant, 22.5% as downstaging and 25.8% as bridging therapy. Milán in= 81% (including effective downstaging), Beyond Milan and UCSF in = 6% and beyond UCSF= 2%. Incidentals=11%. In the explanted liver: non-confirmed HCC 3,3%, beyond Up to 7 criteria 25%, microvascular invasion 16,7 %, macrovascular invasion 6,7%. Imaging accuracy showed that 20% of the patients clinically within Milan criteria exceeded them on pathology. Considering AFP Model, 80% were in criteria. Recurrence-free survival at 1, 3, and 5 years: 94%, 86% and 86%, respectively. Overall Survival at 1, 3 and 5 years: 90%, 75% and 73%, respectively.HCC-related and non-related deaths were 38% (n=7) and 61% (n=11), respectively. Conclusions: Our results are similar when compared to other regional and international data. The AFP model seems to be a good patient selection tool in our setting.